Cooperative Principles Strategy In Buying and Selling At Sasak Traditional Market In Praya - Hijriati, Sartika; Rahman, Lalu Isnaeni; Sugianto, Riris (Universitas Muhammadiyah Mataram, 2023)
This paper focused on analyzing Grice’s maxim as stated in Levinson’s Pragmatics between sellers' and buyers’ conversations during buying and selling activity at the Sasak traditional market in Praya City. The data was collected by recording the speech event using a digital voice recorder and then transcribing the utterances literally. The analysis is done by the pragmatic identity method, then the result is presented using the informal method. The findings reveal 83 instances demonstrated the fulfillment of maxims and 25 exhibited the flouting of maxims. Importantly, participants tended to adhere to maxims more often than deviate from them. Overall, the research indicates adherence to cooperative principles by the speech participants from both the sellers and the buyers to state what they mean clearly and briefly so the conversation flows smoothly. But they also flout the cooperative principles to indirectly send their meaning of utterances. Any utterance they deliver is based on the psychological process that follows principles of normative, behavioral, motivational, and cognitive.